JURNALISME LINGKUNGAN PADA GREEN RADIO 96,7 FM PEKANBARU DALAM PROSES PRODUKSI BERITA TANAMAN JERNANG DI PROGRAM MAJALAH UDARA - Nestina "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Province is known for its environmental problems. Environmental journalism is needed to inform solution. Practic of environmental journalism is doing by Green Radio 96,7 fm Pekanbaru. The preaching of green environmental solution is a priority of Green Radio 96,7 FM Pekanbaru. The existance of this radio culminates in receiving an award from KPID award, which is that Majalah Udara program won the best news of radio Riau in 2016. These achievements certainly cannot be separated from how the process they taking in producing environmental news. One of the interisting reports as a result of the function of deforestation is the news of Jernang. The plants can only grow if the forest is still natural. The research is aiming to see the process of environmental journalism and constraints on the news.This study used qualitative methods of quantitave methods with observation data collection techniques, interviews, and documentation. Data obtained then being processed to be inducted, presented to a public conclution. The informer in this study is five people. The validity of research using an extension of participation and tringulation.The result of this research are, the first news reports live the location and grow and plant breeding plants and news sources are the people of the forests. The process of editing is done by a program in which the publisher used dubbing process, adapting the paragraph so that it does not over 10 minutes, reprocessing the reporter’s data insert, and insert the scene of coverage location. An evaluation of the rapids will be made to write a persona of the many angles. Planning of the news program doesn’t have a clear rundown and deadline. The second is breaking news coverage is the lack of resources and the location of coverage that inhibits the follow up process.